Information, Trade, and Derivative Securities: Table 1 - Brennan, Michael J.; Cao, H. Henry (Review of Financial Studies, 1996)
Hellwig’s (1980) model is used to analyze the value of improving trading opportunities by more frequent trading in the underlying asset, or by trading in a derivative asset. With multiple trading sessions, uninformed investors behave as rational trend followers, while more informed investors follow a contrarian strategy. As trading becomes continuous, Pareto efficiency is achieved. With trading in an appropriate derivative security, Pareto efficiency may be achieved in only a single round of trading. All derivative claims are then priced on Black and Scholes (1973) principles and, in the absence of further supply shocks, no trading will take place in subsequent trading rounds.